2007
DOI: 10.1021/jf0630015
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation and Lactic Acid Addition Enhance Iron Bioavailability of Maize

Abstract: Maize is one of the most important cereal crops for human consumption, yet it is of concern due to its low iron bioavailability. The objective of this study was to determine the effects of processing on iron bioavailability in common maize products and elucidate better processing techniques for enhancing iron bioavailability. Maize products were processed to represent different processing techniques: heating (porridge), fermentation (ogi), nixtamalization (tortillas), and decortication (arepas). Iron and phyta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 25 publications
8
47
1
Order By: Relevance
“…It should be noted that the positive correlation observed between iron solubility with cell transport and uptake efficiencies percentages found in our study is in agreement with Bergqvist et al [26] , studying iron absorption from carrot juice, and with Proulx and Reddy [32] studying iron bioavailability of maize, both using Caco-2 cells. Meanwhile, it has been reported by other authors [27,33] that solubility and bioavailability by Caco-2 cells did not show parallel trends.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that the positive correlation observed between iron solubility with cell transport and uptake efficiencies percentages found in our study is in agreement with Bergqvist et al [26] , studying iron absorption from carrot juice, and with Proulx and Reddy [32] studying iron bioavailability of maize, both using Caco-2 cells. Meanwhile, it has been reported by other authors [27,33] that solubility and bioavailability by Caco-2 cells did not show parallel trends.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, samples fermented with L. rhamnosus, with either B. bifidum (F8) or B. longum (F9), were the ones which induced the most iron uptake (p< 0.05). Previous studies have also shown the in vitro enhancing effect of probiotic bacteria on iron uptake in fermented vegetable matrices, such as carrot juice (Bergqvist, Andlid, & Sandberg, 2006), maize (Proulx & Reddy, 2007) or beans (Laparra, Tako, Glahn, & Miller, 2008). This study, hence, extends the bacterialmediated positive effects on iron uptake from fermented vegetable products, particularly those in which the starter culture contains bifidobacteria strains.…”
Section: Iron Uptake In the Presence Of Fermented Almond Milksupporting
confidence: 64%
“…It has been shown that lactate stimulates fibroblast proliferation (62) and wound healing (59), enhances iron bioavailability in foods (45), and increases iron absorption by the human colon carcinoma cell line (Caco-2 cells) (10). Furthermore, lactic acid has been shown to chelate Fe 3ϩ in a 1:1 ratio (29), and that lactate-iron complex can generate hydroxyl radicals (2).…”
Section: Can Mnsod Protect S Thermophilus Against Acid Stress?mentioning
confidence: 99%